Graphdiyne for Ultrashort Pulse Generation in an Erbium-Doped Hybrid Mode-Locked Fiber Laser - Shi, Zhaojiang; Li, Xiaohui; Zhang, Yani; Li, Hongqi; Zhao, Yang; Guo, Penglai; Guo, Yixuan (Frontiers in Physics, 2019)
An erbium-doped hybrid passively mode-locked fiber laser based on few-layer graphdiyne (GDY) saturable absorber (SA) has been investigated for the first time. Hybrid mode-locked fiber laser is composed of nonlinear polarization rotation (NPR) technology and GDY-SA. The central wavelength, pulse width and repetition rate of the output pulse are 1530.7 nm, 690.2 fs and 14.7 MHz, respectively. Compared with the passively mode-locked pulse laser with GDY-SA or NPR technology alone, the output pulse width of hybrid passively mode-locked fiber laser is reduced more than 50 fs. It is demonstrated that the performance of GDY can be potentially applied in ultrafast laser.